(3eMGPi GdehWCs - (3GdegOi eMeO Hf YHO Gddg Hf JheQJ GdeUehOis; (3GdGeGe eGdc , eGdc Hf CfS Hf eGdc GdGUHMj,J (B179 (3g` s
(3ChdgG (B:s
(3jHOC HHGH GdChbGJ ai GdChbGJ eGdc Hf CfS Yf GHf TgGH Cf YeQ Hf YHO GdYRjR BNQ GdUdGI jheG s
(3BNQgG (B:s
(3jfJgi HGdehLhO efg CKfGA cJGH GdLGeY , ajeG LGA ai GdWYGe hGdTQGH Hbhdg (B: (3GdCeQ HGdQbjI ef GdYjf s
(3LGA HChdgG agQS ddcJH GdJi JVefJgGs
(3cJHJ GdfSNI Ydi Qb ZRGd ef JMHjS bGFO GdSbja CjGe Hfi eQ Hf CHj eMeO YHO Gddg GdWQjai YGe (B811(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B257 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B168s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG RNGQa s
Keywords: (3GdMOjK h GdeUWdMs